2002
DOI: 10.1080/110241502321116433
|View full text |Cite
|
Sign up to set email alerts
|

Lichtenstein Repair for Incarcerated Groin Hernias

Abstract: Monofilament polypropylene mesh can be successfully used not only in elective operations, but also in emergency operations for incarcerated inguinal hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
(19 reference statements)
1
15
0
9
Order By: Relevance
“…This is comparable to the 4% postoperative morbidity after hernioplasty for acutely incarcerated inguinal hernias reported by Wysocki et al 4 Incarcerated hernia can predispose to wound infection, 8 but wound infections are often managed effectively by antibiotic therapy with or without drainage.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This is comparable to the 4% postoperative morbidity after hernioplasty for acutely incarcerated inguinal hernias reported by Wysocki et al 4 Incarcerated hernia can predispose to wound infection, 8 but wound infections are often managed effectively by antibiotic therapy with or without drainage.…”
Section: Discussionsupporting
confidence: 66%
“…2 However, there are few reports on the surgical outcomes of emergency hernioplasty for incarcerated inguinal hernia. 3,4 The aim of this study was to evaluate the short-term and long-term outcomes of emergency Lichtenstein tension-free hernioplasty for acutely incarcerated inguinal hernia.…”
Section: Introductionmentioning
confidence: 99%
“…Strangulated hernias have been deemed to be an absolute contraindication for the use of a prosthetic mesh [2]. Some groups, however, have reported that a strangulated groin hernia can be repaired safely with a prosthetic mesh [2][3][4][5][6][7]. There is no consensus on the use of prostheses in potentially infected operating fields (after intestinal resection) [8].…”
Section: Introductionmentioning
confidence: 97%
“…The primary repair of inguinal hernias is generally performed using the technique described by Lichtenstein and many studies that used this technique have been published [5]. While the use of mesh in emergency conditions (strangulation) is questioned, the number of reports stating the efficacy and reliability of mesh use in these conditions are increasing [1,2,6]. In addition to their use in elective hernias, polypropylene mesh can also be used in cases of strangulated hernia with acceptable post-operative complication rates [1][2][3].…”
Section: Discussionmentioning
confidence: 99%